Corporate social responsibility and innovative work behavior: Is it a matter of perceptions?. (22nd June 2022) - Alhmoudi, Ranya Saeed; Singh, Sanjay Kumar; Caputo, Francesco; Riso, Teresa; Iandolo, Francesca
Abstract: The paper investigates the influence of corporate social responsibility (CSR) on Innovative Work Behavior (IWB). The mediating role of passion and organizational commitment is investigated for understanding the effect of CSR on companies' performances by adopting a behavioral perspective. Based on the exploratory literature review conducted during the period from 1990 to 2020 and the content analysis method, we explore possible relationships among CSR, human capital, relational capital, and innovative work behaviors. Building upon the evidence from the literature review, a set of propositions have been defined for supporting both researchers and practitioners in enhancing the potential contribution of perceived CSR to improve companies' performance by adopting IWBs. The paper enriches ongoing debate about CSR's influence on companies' performances investigating the pivotal role of perceptions about CSR practices in influencing IWBs within the business field.